THE WEST AND THE CONFLICT IN NAGORNY KARABAKH - BABAIAN, David (CENTRAL ASIA AND THE CAUCASUS, 2004)
The Nagorno-Karabakh conflict can be de-scribed as the most persistent and difficult to resolve among the post-Soviet conflicts. This is mainly explained by the geopolitical dilemma that becomes evident every time an attempt is made to settle it. I have in mind the conflict between geography and ideology, the two sides of geopolitics. The geographic side relates to geographic location, mineral riches, etc., while ideology is related to values, culture, world outlook, and history. A conflict can potentially be promptly settled if one of the sides obviously dominates in both respects; it may drag on and on if neither side predominates, or if one of them dominates geographically, while the other, ideologically. Any protracted conflict does not always mean protracted fighting. A conflict can be frozen, while the sides are left to their more or less peaceful existence. More often than not this is described as a “neither war, nor peace "situation. The Nagorno-Karabakh conflict differs from many other conflicts because the sides involved have different, yet mutually balanced, geopolitical advantages. Azerbaijan’s geographic location is obviously much more advantageous than that of Nagorny Karabakh (the former, found between Russia and Iran, serves as a bridge to Central Asia).n top of this, it is rich in oil and gas. Nagorny Karabakh dominates in the ideological respects, which balances out Azerbaijan’s geographic advantages. This balance between the geographic and ideological components can be clearly detected in Western policies in the Southern Caucasus. To ac-quire a better understanding let us discuss the main imperatives of the key Western players in the context of the Nagorno-Karabakh settlement process.